Assistance and Education of Community Perception Related to Covid-19 Vaccine in Benteng Kelurahan, Ciamis District, Ciamis Regency - Lilis Lismayanti; Rudi Kurniawan; Yanti Srinayanti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
At the beginning of 2020, the whole world was shocked by the outbreak of a new virus, namely the corona virus which was suspected to be a new type of SARS COV-2. The Indonesian government has made various efforts to overcome the COVID-19 pandemic, including plans to provide a Covid-19 vaccine, but the public's main concern is on the safety and effectiveness of the vaccine, and whether the vaccine will be considered halal. Therefore, according to the review above, the researcher wants to carry out community service related to the perception of the covid-19 vaccine in the Benteng Village in order to have access to accurate information about the safety and effectiveness of the vaccine. This community service method is counseling and assistance to partners. The results of the activity showed that the community was very enthusiastic about participating in the Covid-19 vaccine counseling according to an Islamic view which contained information about the vaccine program, safety, halalness and effectiveness of the Covid-19 vaccine and actively participated in discussions and Q&A with companions. In conclusion, the Covid-19 Vaccine health education can increase public knowledge about the Covid-19 vaccine according to the Islamic view